Investigation of AC losses in horizontally parallel HTS tapes. (12th June 2017) - Shen, Boyang; Li, Jing; Geng, Jianzhao; Fu, Lin; Zhang, Xiuchang; Zhang, Heng; Li, Chao; Grilli, Francesco; Coombs, T A
Abstract: This paper presents an AC loss study of horizontally parallel HTS tapes. We proposed to use three parallel HTS tapes as an example. The AC losses of the middle and end tape of three parallel tapes have been measured using the electrical method and compared to those of an individual tape. The effect of the interaction between tapes on AC losses has been analysed, and compared with finite-element method (FEM) simulations using the 2D H -formulation implemented in COMSOL Multiphysics. By using FEM simulations, the cases of increasing number of parallel tapes have been considered, and the normalised ratio between the total average AC losses per tape and the AC losses of an individual single tape has been calculated for different gap distances. We proposed a new parameter, Ns, a turning point for number of tapes, to divide Stage 1 and Stage 2 for the AC loss study of horizontally parallel tapes. For Stage 1, N  <  Ns, the total average losses per tape increased with the increasing number of tapes. For Stage 2, N  >  Ns, the total average losses per tape decrease with the increasing number of tapes. The analysis demonstrates that horizontally parallel HTS tapes could be potentially used in superconducting devices like HTS transformers, which could retain or even reduce the total average AC losses per tape with large number of parallel tapes.